2006
DOI: 10.1007/s00442-006-0574-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizer and gender effects on the secondary metabolism of yaupon, a caffeine-containing North American holly

Abstract: Yaupon (Ilex vomitoria) is a caffeine-containing dioecious shrub native to the southeastern United States that was historically brewed into a stimulating beverage. We tested predictions of the carbon/nutrient balance (CNB) hypothesis by determining whether nitrogen availability and gender influence production of caffeine and related alkaloids as well as phenolic compounds in leaves of pot-grown yaupon plants fertilized with ammonium nitrate. The CNB hypothesis predicts that additional nitrogen should result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…Under these conditions, the significant increase of TP can be interpreted as: photosynthesis surpasses the growth demand, and, on there being an excess of carbohydrates that accumulate in plants with nitrate deficiency, the C assimilated is available for biosynthesis of compounds that do not require N (e.g., phenolics). Phenolic accumulation due to light increase or nitrate deficiency has been reported in different studies (Briskin and Gawienowski 2001;Coviella et al 2002;Mosaleeyanon et al 2005;Fritz et al 2006;Poorter et al 2006;Grechi et al 2007;Palumbo et al 2007;Le Bot et al 2009). Under high-irradiance and nitrate-deficiency conditions, the assimilated carbon is directed toward the following two key components: (a) the biomass increase in roots, as previously mentioned, and (b) toward the increase of levels of carbon-rich secondary metabolites, such as phenolics.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Under these conditions, the significant increase of TP can be interpreted as: photosynthesis surpasses the growth demand, and, on there being an excess of carbohydrates that accumulate in plants with nitrate deficiency, the C assimilated is available for biosynthesis of compounds that do not require N (e.g., phenolics). Phenolic accumulation due to light increase or nitrate deficiency has been reported in different studies (Briskin and Gawienowski 2001;Coviella et al 2002;Mosaleeyanon et al 2005;Fritz et al 2006;Poorter et al 2006;Grechi et al 2007;Palumbo et al 2007;Le Bot et al 2009). Under high-irradiance and nitrate-deficiency conditions, the assimilated carbon is directed toward the following two key components: (a) the biomass increase in roots, as previously mentioned, and (b) toward the increase of levels of carbon-rich secondary metabolites, such as phenolics.…”
Section: Discussionmentioning
confidence: 95%
“…Under conditions of high photosynthesis rate or reduction of available nitrogen (N), production of C-based defense compounds will be favored, whereas under the opposite conditions, N-based defense compound synthesis will be carried out (Coviella et al 2002;Fritz et al 2006;Grechi et al 2007). According to these predictions, it has been demonstrated that the production of phenolics can be stimulated by low nitrate levels (Armstrong et al 1970;Fritz et al 2006;Palumbo et al 2007;Le Bot et al 2009), high light (Hemm et al 2004;Jaakola et al 2004;Mosaleeyanon et al 2005) and other biotic and abiotic stresses, e.g., pathogen attack, mechanic wounding, ultraviolet (UV) radiation, low temperatures and nutrient deficit (Bernards and Ellis 1991;Kováčik and Bačkor 2007;Clé et al 2008;Jansen et al 2008). Phenylalanine ammonia-lyase enzyme (PAL) catalyzes the conversion of phenylalanine into trans-cinnamic acid; therefore, this enzyme causes the flux of primary into secondary metabolites in the phenolics pathway.…”
Section: Introductionmentioning
confidence: 90%
“…Yet our results do not support this hypothesis; although growth was constrained in the Effect of nitrogen fertilization on caffeine production in coffee (Coffea arabica) 127 low-N treatment we observed no difference in caffeine concentration and content across N treatments. Contrastingly, Palumbo et al (2007), found caffeine concentration in leaf tissues of Ilex vomitoria increased with N fertilization, which suggests that the caffeine phenotype is influenced by environmental factors for some plants. Yet another study conducted with coffee, supported our study's findings.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, higher production of SMs may lead to reduced plant growth or reproduction (Karban and Baldwin 1997). Further, energy and nutrients may limit the ability of plants to produce SMs under different environmental conditions (Bryant et al 1983;Herms and Mattson 1992;Dyer et al 2004;Palumbo et al 2007; but see Hamilton et al 2001). Globally, it is predicted that plants living in environments that are limited by N availability will evolve carbon (C)-based defenses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation